Empowering Listening Comprehension through Pre-Listening Strategies: An Action Research Study on EFL Learners - Ruisah (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
Listening comprehension remains one of the most challenging language skills for English as a Foreign Language (EFL) learners. This action research study explores the impact of pre-listening language learning strategies on the listening comprehension skills of first-semester students at Universitas Pamulang. A total of 35 students participated in a structured intervention comprising three cycles of strategy-based listening instruction. Data were collected through observation forms, researcher-practitioner journals, and semi-structured interviews. Descriptive and content analyses were employed to interpret the data. The findings reveal that the explicit teaching of pre-listening strategies significantly improved learners’ motivation, comprehension, and engagement with listening tasks. Students reported increased confidence, enhanced understanding of listening texts, and reduced anxiety. Although a few learners faced challenges in recalling prior knowledge or vocabulary, the majority expressed positive attitudes toward the approach. The study highlights the value of incorporating pre-listening strategies as an integral component of EFL instruction to support listening development and learner autonomy.